2011
DOI: 10.1186/1752-0509-5-67
|View full text |Cite
|
Sign up to set email alerts
|

A modulated empirical Bayes model for identifying topological and temporal estrogen receptor α regulatory networks in breast cancer

Abstract: BackgroundEstrogens regulate diverse physiological processes in various tissues through genomic and non-genomic mechanisms that result in activation or repression of gene expression. Transcription regulation upon estrogen stimulation is a critical biological process underlying the onset and progress of the majority of breast cancer. Dynamic gene expression changes have been shown to characterize the breast cancer cell response to estrogens, the every molecular mechanism of which is still not well understood.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…As previous investigations have shown [17, 20], many hubs in differential interaction network serve as key components of cancer-associated pathways and can be used to discover cancer-induced genes. Our experimental results on breast cancer data also demonstrated that two such differential network hubs, DCK and BBC3 , link to MAPK signaling pathway and metastasis, as reported in [21, 22].…”
Section: Methodsmentioning
confidence: 99%
“…As previous investigations have shown [17, 20], many hubs in differential interaction network serve as key components of cancer-associated pathways and can be used to discover cancer-induced genes. Our experimental results on breast cancer data also demonstrated that two such differential network hubs, DCK and BBC3 , link to MAPK signaling pathway and metastasis, as reported in [21, 22].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a catalogue of direct binding targets of PPARα with functional PPREs in their promoter was used (Mandard et al 2004; Heinaniemi et al 2007; Rakhshandehroo et al 2010) to assign differentially expressed genes to three groups based on their mechanism of regulation (Shen et al 2011):Direct genomic binding (DGB), where PPARα induces gene transcription by binding to PPREs in the promoters of target genes, corresponding to the “canonical” mode of action.Indirect genomic binding (IDGB), whereby PPARα is bound to promoter regions of target genes, but not to PPREs—presumably through protein–protein interactions with other transcription factors that directly bind DNA. This “tethering” mechanism has been observed with other NRs like the GR and ER, where it may account for the regulation of 25–30 % of target genes (George et al 2011; Heldring et al 2007; So et al 2007; Stender et al 2010).…”
Section: Use Of In Vitro Systems For Predicting Liver Toxicitymentioning
confidence: 99%
“…Predicting the transcription factors responsible for a cellular response would significantly contribute to PoT identification (Essaghir et al 2010; Shen et al 2011; Maertens et al 2015). However, traditional approaches for identifying transcription factors from gene expression patterns use data from a small subset of the genome.…”
Section: Introductionmentioning
confidence: 99%